What happens to microglial TREM2 in Alzheimer's disease: Immunoregulatory turned into immunopathogenic?. (27th August 2015) - Lue, L.-F.; Schmitz, C.; Walker, D.G.
Highlights: Mutations in TREM2 gene increase the risk of several neurodegenerative diseases. As a phagocytic receptor, TREM2 also regulates inflammatory responses in microglia. Elevated expression of TREM2 is associated with Alzheimer's disease pathology. Current literature on non-mutated TREM2 in the brain and microglia are reviewed. Abnormal TREM2 functions could cause activated microglia to be immunopathogenic. Abstract: Microglia play major roles in initiation, coordination and execution of innate immunity in the brain. In the adult brain, these include maintenance of homeostasis, neuron and tissue repair, and eliminating infectious agents, apoptotic cells, and misfolded proteins. Some of these activities are accompanied by inflammatory reactions; and others are performed with no inflammatory effects. Under normal conditions, triggering receptor expressed on myeloid cells 2 (TREM2) belongs to the second category. It pairs with the adaptor protein DNAX-activating protein of 12 kDa (DAP12) to induce phagocytosis of apoptotic neurons without inflammatory responses, and to regulate Toll-like receptor-mediated inflammatory responses, and microglial activation. Although ligands for TREM2 are largely unknown, the mitochondrial heat shock protein 60, expressed on cell surface of apoptotic neurons, is a specific ligand that activates TREM2-mediated phagocytosis by microglia. TREM2 also phagocytoses amyloid beta peptide in cultured cells. Several TREM2 mutations have been identified recently that increase the risk of Alzheimer's disease, Frontotemporal dementia, Parkinson's disease, and amyotrophic lateral sclerosis. Some of these mutations cause impaired proteolysis of full-length TREM2 at the plasma membrane to different degrees. The defects in the intramembrane cleavage result in dysfunction of phagocytosis signaling. The association of TREM2 mutations with neurodegenerative disease also calls for the understanding of the biology and pathological role of non-mutated TREM2 on human brains and microglia. This review provides a summary of current literature in TREM2 and DAP12 from several aspects, and proposes a theory that loss of TREM2 functions might contribute to the immunopathogenic role of microglia in Alzheimer's disease.